Photocatalytic coating for vase and preparation method thereof
By applying a photocatalytic coating of composite film layers on the vase, combined with radio frequency magnetron sputtering technology and light storage luminous materials, the problem of single functions of traditional vases is solved, and the functions of degrading pollutants day and night, purifying water resources and automatic luminescence at night are realized.
Patent Information
- Application Number
- CN202411951756.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional vases have a single function, making it difficult to effectively degrade bacterial silt in the bottle and purify water resources, and at the same time lack the functions of night photocatalysis and plant fluorescence emission.
A photocatalytic coating of a composite film layer is adopted, including the inner layer consisting of SiC, ZnO and TiO2, and the outer layer consists of Ag, N4C3, Al2O3, ZnO and TiO2. It is prepared by radio frequency magnetron sputtering technology, combined with light-storage luminescent materials to achieve photocatalytic degradation and automatic luminescence at night.
The photocatalytic coating can degrade pollutants day and night, purify the water resources inside the vase, kill bacteria and antibacterial, and automatically emit light in the dark, enhancing the night fluorescence effect of the plants.
Abstract
Description
Technical Field
[0001] The invention relates to a vase, in particular to a photocatalytic coating for a vase and a preparation method thereof. Background Art
[0002] Traditional vases are usually used to hold fresh or dried flowers and as interior decorations. Their main functions are to beautify the home environment, increase the atmosphere of the room and improve the air quality. However, the existing traditional vases have relatively single functions.
[0003] Photoluminescent materials rarely use radioactive substances. They mainly rely on absorbing external light energy and then slowly releasing it. They need to store enough light energy to ensure continuous luminescence for a period of time. Their use is basically unrestricted, but their brightness is not as good as that of self-luminous materials. In recent years, photoluminescent materials have developed in the direction of being non-toxic and non-radiative. The brightness of photoluminescent materials obtained by high-temperature sintering of aluminum, barium and strontium series with rare earth elements is hundreds of times that of traditional materials. This type of coating absorbs and stores light energy under the irradiation of visible light such as sunlight or lamplight. After the light stops, the absorbed energy is slowly released in the form of visible light, and then the process of absorbing light, storing light, emitting light and absorbing light is repeated. As one of the special functional coatings in the 21st century, photoluminescent coatings have the advantages of ultra-long afterglow, high luminous brightness and long luminous time. They are widely used and have been applied to architectural decoration, automobile decoration, road signs, billboards and other aspects. Summary of the invention
[0004] The purpose of the present invention is to provide a photocatalytic coating for vases and a preparation method thereof. The coating is used to degrade bacterial sludge in the bottle and purify water resources; the light-storage luminous material contained in the coating is used to store light and heat, convert it into light energy for storage, and then automatically emit light in the dark to achieve nighttime photocatalysis, and can also make plants emit fluorescence at night.
[0005] To achieve the above object, the present invention adopts the following technical solutions: A photocatalytic coating for a vase, the photocatalytic coating is a composite film layer arranged on the surface of a glass substrate, the composite film layer comprises an inner layer and an outer layer in sequence from the inside to the outside, the inner layer is formed of 70wt% SiC, 10wt% ZnO and 20wt% TiO2, and the outer layer is formed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO and 70wt% TiO2.
[0006] Furthermore, the thickness of the inner layer is 50-100 nm.
[0007] Furthermore, the thickness of the outer layer is 25-50 nm.
[0008] Furthermore, the thickness of the glass substrate is 5-10 mm.
[0009] Furthermore, the outer layer material of the photocatalytic coating is composed of the following components in mass percentage: 65-95% of photocatalytic degradation material, 5-35% of light-storage luminous material, and the sum of the mass percentages of the above components is 100%. Among them, the light-storage luminous material is selected from zinc sulfide, rare earth activated alkaline earth metal aluminate or rare earth doped silicate luminescent material (including alkaline earth aluminate, silicate, aluminum oxide, strontium carbonate, barium sulfate, barium carbonate, strontium lanthanum manganate, strontium lanthanum cobaltate system) with a particle size of 100-200nm. The photocatalytic degradation material includes: aluminum oxide, zinc oxide, silver, titanium dioxide or two or more synthetic compounds, with a particle size of 50 nm-100nm.
[0010] The method for preparing a photocatalytic coating for a vase according to the present invention comprises the following steps: 1) Surface treatment of the glass substrate: ultrasonically clean the substrate in deionized water and ethanol for 30 min respectively, and then blow dry with nitrogen; 2) Preparation of inner layer: The substrate is sent into the coating chamber, and an inner layer composed of 70wt% SiC, 10wt% ZnO, and 20wt% TiO2 is formed by RF magnetron sputtering. A DC power supply is used, the sputtering power is 100~200W, Ar gas is used as the protective gas, ZnO, TiO2, and SiC are used as targets, the ZnO target current is 1~8A, the SiC target current is 4~8A, the TiO2 target current is 2~4A, the Ar gas flow rate is 100~200sccm, the substrate revolution is 2~4rpm, the sputtering time is 10~30min, and the distance between the target and the substrate is 40~80mm; 3) Preparation of outer layer: Continue RF magnetron sputtering to form an outer layer composed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO, and 70wt% TiO2, using a DC power supply, a sputtering power of 100~200W, Ar gas as a protective gas, Ag, Al2O3, ZnO, TiO2 and N4C3 as targets, ZnO target current 1~3A, N4C3 target current 4~8A, TiO2 target current 2~4A, Al2O3 target current 1~2A, Ag target current 0~1A, Ar gas flow rate 100~200sccm, substrate revolution 2~4rpm, sputtering time 10~30min, and the distance between the target and the substrate 40~80mm.
[0011] The semiconductor photocatalytic material titanium dioxide (TiO2) has been widely used in solar cells, efficient degradation of organic wastewater under ultraviolet light, air purification and other fields due to its low price and stable performance. Its application has attracted more and more attention. The photocatalytic degradation of organic wastewater by TiO2 is regarded as a research hotspot for solving environmental and global energy supply problems. However, its band gap energy is large, and electrons and holes in the microstructure are easily recombined, which causes a decrease in the yield of highly active oxidized groups, and then leads to a decrease in catalytic ability. Therefore, appropriate modification of the TiO2 catalyst is beneficial to the improvement of its photocatalytic performance. The band gap width of nano-titanium dioxide is 3.2eV. Under ultraviolet light irradiation conditions, electrons are excited from the low energy band to the high energy band conduction band to form highly active electrons e - , and leaves a positively charged hole h in the low energy band + , highly active electrons - and positively charged holes h + With OH - , H2O, and O2 come into contact to form highly active OH• groups and O 2- Groups, which have non-selective oxidation ability for various pollutants in the photocatalytic process. However, TiO2 is a wide bandgap semiconductor compound, which is only active in ultraviolet light, while ultraviolet light (300-400 nm) only accounts for about 5% of the solar energy reaching the ground, while visible light accounts for 45% of the total solar energy. In order to improve the utilization rate of solar energy, the visible light activity of TiO2 must be improved. In addition, nano-titanium dioxide has good photocatalytic degradation effect and can perform photocatalytic redox degradation reactions on various inorganic and organic pollutants in air and water.
[0012] Silicon carbide (SiC) has two commonly used basic varieties: black silicon carbide and green silicon carbide, both of which belong to α-SiC. Black silicon carbide contains about 95% SiC, and its toughness is higher than that of green silicon carbide. It is mostly used to process materials with low tensile strength, such as glass, ceramics, stone, refractory materials, cast iron and non-ferrous metals. The SiC layer has a high refractive index, stable chemical properties, strong film adhesion, and can form a good bond with the surface of the glass substrate; it has high transmittance in the visible light region and high absorption rate in the ultraviolet region, and has ideal transparent and heat-insulating properties. The band gap width of SiC is 2-3 times that of Si, the thermal conductivity is about 4.4 times that of Si, the critical breakdown electric field is about 8 times that of Si, and the saturated drift velocity of electrons is 2 times that of Si.
[0013] ZnO is an important n-type semiconductor. It has a wide source, is non-toxic and inexpensive. Its bandgap is about 3.2 eV. Under ultraviolet light, it can stimulate the generation of photogenerated electron-hole pairs to generate ·OH and ·O2 -Highly active groups with strong redox ability can degrade organic pollutants such as dyes. Due to the easy recombination of photogenerated electron-hole pairs generated by pure ZnO, the photocatalytic activity is reduced, and photochemical corrosion is prone to occur during the photocatalytic process, which is not conducive to its actual large-scale industrial utilization. ZnO is currently a widely studied n-type semiconductor photocatalyst, but it cannot fully meet the light stability, chemical stability, high selectivity and high catalytic efficiency required by semiconductor photocatalysts with industrial application value. It also requires factors such as appropriate material cost and light matching performance. Therefore, improving the photocatalytic activity and stability of ZnO through the study of its composition and structure is one of the hot spots in the current photocatalytic research field.
[0014] The purpose of doping non-metallic ions is to reduce the bandgap of semiconductors and expand the wavelength response range of TiO2 semiconductors to make them responsive to visible light. Non-metallic ion doped TiO2 photocatalysts have attracted extensive attention and research in the academic community. Among them, carbon nitride (N4C3) materials not only have high visible light utilization efficiency, but are also non-toxic and harmless, have high chemical and thermal stability, and are made of cheap and readily available raw materials and simple preparation processes. They have broad application prospects in the use of clean energy and catalytic purification of the environment.
[0015] The above technical scheme adopted by the present invention has the following technical effects: the present invention uses ZnO / TiO2 as a carrier, and on this carrier, a modified light-storage type luminous material is loaded, including metal element doping, non-metal element doping, oxide coupling and precious metal doping, etc. to obtain a ZnO / TiO2 composite photocatalyst with strong photocatalytic performance; the photocatalyst is excited by the loaded light-storage type luminous material under visible light, and the use and utilization rate of the photocatalyst at night are improved, and it contacts with organic pollutant molecules and interacts with each other to achieve a catalytic or conversion effect, so that the surrounding oxygen and water molecules are excited into free negative ions with strong oxidizing power, thereby achieving the purpose of degrading harmful organic substances in the environment.
[0016] Compared with the prior art, the present invention has the following beneficial effects: the present invention sets a photocatalytic coating layer inside the vase, which can degrade pollutants day and night, treat and purify water resources inside the vase, purify air, and sterilize and resist bacteria. Among them, the photocatalytic coating is used to degrade bacterial sludge in the bottle and purify water resources; the light-storage luminous material coating is used to store light and heat, convert it into light energy storage, and then automatically emit light in the dark, realizing nighttime photocatalysis, and can also make plants emit fluorescence at night. DETAILED DESCRIPTION
[0017] A photocatalytic coating for a vase, the photocatalytic coating is a composite film layer arranged on the surface of a glass substrate, the composite film layer includes an inner layer and an outer layer from the inside to the outside, the inner layer is formed by 70wt% SiC, 10wt% ZnO and 20wt% TiO2, and the outer layer is formed by 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO and 70wt% TiO2. The thickness of the inner layer is 50-100nm, the thickness of the outer layer is 25-50nm, and the thickness of the glass substrate is 5-10mm. Example 1
[0018] A method for preparing a photocatalytic coating for a vase comprises the following steps: 1) Surface treatment of the glass substrate: ultrasonically clean the substrate in deionized water and ethanol for 30 min respectively, and then blow dry with nitrogen; 2) Preparation of inner layer: The substrate was sent into the coating chamber, and an inner layer composed of 70wt% SiC, 10wt% ZnO, and 20wt% TiO2 was formed by RF magnetron sputtering. A DC power supply was used, the sputtering power was 100W, Ar gas was used as the protective gas, ZnO, TiO2, and SiC were used as targets, the ZnO target current was 1A, the SiC target current was 4A, the TiO2 target current was 2A, the Ar gas flow rate was 100sccm, the substrate revolution was 2rpm, the sputtering time was 10min, and the distance between the target and the substrate was 40mm; 3) Preparation of outer layer: Continue RF magnetron sputtering to form an outer layer composed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO, and 70wt% TiO2, using a DC power supply, a sputtering power of 100W, Ar gas as a protective gas, Ag, Al2O3, ZnO, TiO2 and N4C3 as targets, ZnO target current 1A, N4C3 target current 4A, TiO2 target current 2A, Al2O3 target current 1A, Ag target current 0A, Ar gas flow rate 100sccm, substrate revolution 2rpm, sputtering time 10min, the distance between the target and the substrate is 40mm. Example 2
[0019] A method for preparing a photocatalytic coating for a vase comprises the following steps: 1) Surface treatment of the glass substrate: ultrasonically clean the substrate in deionized water and ethanol for 30 min respectively, and then blow dry with nitrogen; 2) Preparation of inner layer: The substrate was sent into the coating chamber, and an inner layer composed of 70wt% SiC, 10wt% ZnO, and 20wt% TiO2 was formed by RF magnetron sputtering. A DC power supply was used, the sputtering power was 200W, Ar gas was used as the protective gas, ZnO, TiO2, and SiC were used as targets, the ZnO target current was 2A, the SiC target current was 8A, the TiO2 target current was 4A, the Ar gas flow rate was 200sccm, the substrate revolution was 4rpm, the sputtering time was 30min, and the distance between the target and the substrate was 80mm; 3) Preparation of outer layer: Continue RF magnetron sputtering to form an outer layer composed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO, and 70wt% TiO2, using a DC power supply, a sputtering power of 200W, Ar gas as a protective gas, Ag, Al2O3, ZnO, TiO2 and N4C3 as targets, ZnO target current 3A, N4C3 target current 8A, TiO2 target current 4A, Al2O3 target current 2A, Ag target current 1A, Ar gas flow rate 200sccm, substrate revolution 4rpm, sputtering time 30min, the distance between the target and the substrate is 80mm. Example 3
[0020] A method for preparing a photocatalytic coating for a vase comprises the following steps: 1) Surface treatment of the glass substrate: ultrasonically clean the substrate in deionized water and ethanol for 30 min respectively, and then blow dry with nitrogen; 2) Preparation of inner layer: The substrate was sent into the coating chamber, and RF magnetron sputtering was used to form an inner layer composed of 70wt% SiC, 10wt% ZnO, and 20wt% TiO2. A DC power supply was used, the sputtering power was 150W, Ar gas was used as the protective gas, ZnO, TiO2, and SiC were used as targets, the ZnO target current was 2A, the SiC target current was 6A, the TiO2 target current was 3A, the Ar gas flow rate was 150sccm, the substrate revolution was 3rpm, the sputtering time was 20min, and the distance between the target and the substrate was 40mm; 3) Preparation of outer layer: Continue RF magnetron sputtering to form an outer layer composed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO, and 70wt% TiO2, using a DC power supply, a sputtering power of 100W, Ar gas as a protective gas, Ag, Al2O3, ZnO, TiO2 and N4C3 as targets, ZnO target current 2A, N4C3 target current 6A, TiO2 target current 3A, Al2O3 target current 1.5A, Ag target current 0.5A, Ar gas flow rate 15sccm, substrate revolution 3rpm, sputtering time 20min, the distance between the target and the substrate is 60mm.
[0021] In order to verify the photocatalytic coating for vases prepared by the preparation method of the present invention, performance tests were performed on the composite film layers in the above embodiments.
[0022] According to the test of the coating layer adhesion of the coating, the adhesion is 3.0-5.5N; 3M tape adhesion test: no falling off; water resistance test for 96h, the coating has no abnormality, no blistering, no peeling, no discoloration; when testing the coating's light resistance, the sample is placed under a high-pressure mercury lamp for continuous irradiation for 72h, and the appearance color change of the coating before and after irradiation is compared. It is known that there is no abnormality; the photocatalytic activity test of methyl orange was carried out on the photocatalytic coating in the prepared vase using an ultraviolet visible spectrophotometer (UV-2102PC, UNICO Company). The photocatalytic degradation effect of the sample within 30 minutes reached 95%, and the degradation rate reached 90% after 3 hours of illumination. In addition, after the catalytic coating is recycled for more than 5 times, the photocatalytic performance can still maintain a degradation rate of more than 85%. The test board was prepared according to the standard of GB / T9779-2015 and tested with a long afterglow fluorescence tester. The test showed that the afterglow time of the coating reached more than 15h, and the afterglow brightness reached 650 mcd / m 10s after the excitation. 2 above.
Claims
1. A photocatalytic coating for a vase, characterized in that: The photocatalytic coating is a composite film layer arranged on the surface of a glass substrate, and the composite film layer includes an inner layer and an outer layer in sequence from the inside to the outside, the inner layer is formed of 70wt% SiC, 10wt% ZnO and 20wt% TiO2, and the outer layer is formed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO and 70wt% TiO2.
2. The photocatalytic coating for a vase according to claim 1, characterized in that: The thickness of the inner layer is 50-100 nm.
3. The photocatalytic coating for a vase according to claim 1, characterized in that: The thickness of the outer layer is 25-50 nm.
4. The photocatalytic coating for a vase according to claim 1, characterized in that: The thickness of the glass substrate is 5-10 mm.
5. The method for preparing a photocatalytic coating for a vase according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Surface treatment of glass substrate; 2) Preparation of inner layer: The substrate is sent into the coating chamber, and an inner layer composed of 70wt% SiC, 10wt% ZnO, and 20wt% TiO2 is formed by RF magnetron sputtering. A DC power supply is used, the sputtering power is 100~200W, Ar gas is used as the protective gas, ZnO, TiO2, and SiC are used as targets, the ZnO target current is 1~8A, the SiC target current is 4~8A, the TiO2 target current is 2~4A, the Ar gas flow rate is 100~200sccm, the substrate revolution is 2~4rpm, the sputtering time is 10~30min, and the distance between the target and the substrate is 40~80mm; 3) Preparation of outer layer: Continue RF magnetron sputtering to form an outer layer composed of 5wt% Ag, 5wt% N4C3, 10wt% Al2O3, 10wt% ZnO, and 70wt% TiO2, using a DC power supply, a sputtering power of 100~200W, Ar gas as a protective gas, Ag, Al2O3, ZnO, TiO2 and N4C3 as targets, ZnO target current 1~3A, N4C3 target current 4~8A, TiO2 target current 2~4A, Al2O3 target current 1~2A, Ag target current 0~1A, Ar gas flow rate 100~200sccm, substrate revolution 2~4rpm, sputtering time 10~30min, and the distance between the target and the substrate 40~80mm.
6. The method for preparing a photocatalytic coating for a vase according to claim 5, characterized in that: The step 1) is specifically as follows: the glass substrate is ultrasonically cleaned in deionized water and ethanol for 30 minutes respectively, and then blown dry with nitrogen.